2005
DOI: 10.1128/jcm.43.10.4972-4976.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Invasive Pneumococcal Infection by Serotype-Specific Urinary Antigen Detection

Abstract: Widespread use of conjugate pneumococcal polysaccharide-protein vaccines may alter the spectrum of pneumococci producing invasive disease. Novel sensitive diagnostic methods would be valuable for monitoring the epidemiology of pneumococcal disease within populations and vaccine recipients. Ideally, these methods should allow determination of the serotype of the infecting clone. Serotype-specific enzyme-linked immunosorbent assays (ELISA) for 13 capsular polysaccharides (types 1, 3, 4, 5, 6A, 6B, 7A, 9V, 14, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Serotype-specific antigen detection in urine has been attempted before, with excellent specificity (98-99%), but disappointing sensitivity (55-84%), when compared with S. pneumoniae isolates detected in sterile sites [19][20][21][22]. The sensitivity of the ICA test in the present study was 63%.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Serotype-specific antigen detection in urine has been attempted before, with excellent specificity (98-99%), but disappointing sensitivity (55-84%), when compared with S. pneumoniae isolates detected in sterile sites [19][20][21][22]. The sensitivity of the ICA test in the present study was 63%.…”
Section: Discussionsupporting
confidence: 49%
“…However, at this point, there is no other reference standard to better test accuracy of serotype specific diagnostic tools. Secondly, pneumococcal antigens can persist in urine samples after infection for periods as long as from 7 days [19,29] to 3 months [30]. Although we did not have detailed information about disease history in the weeks before the clinical episode of CAP, we could determine that only eight (0.7%) patients had been hospitalised in the weeks before the CAP episode.…”
Section: Discussionmentioning
confidence: 93%
“…Serotype-specific identification assays have previously been reported and include assays based on latex agglutination (28) and enzyme-linked immunosorbent assay (ELISA) (17). Leeming et al (17) reported on an ELISA capable of detecting serotype-specific polysaccharide in urine, but this assay is dependent upon the availability of MAbs with high degrees of specificity for pneumococcal capsular polysaccharides which are not commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…While this assay is rapid (15-min performance time), the BinaxNOW S. pneumoniae urine antigen test measures the presence only of the C-PS antigen, which is present on all S. pneumoniae strains, and does not distinguish between the different serotypes of this organism. In addition, the sensitivity of this method has also been called into question by users in the field (27,43).…”
mentioning
confidence: 99%